Pt catalyzed formation of a Ni@Pt/reduced graphene oxide nanocomposite: preparation and electrochemical sensing application for glucose detection. Issue 31 (31st July 2018) - Ma, Lian; Wang, Xiaoyan; Zhang, Qiaran; Tong, Xinli; Zhang, Yue; Li, Zhuang
Abstract : In this work, a Ni@Pt/rGO nanocomposite was prepared for the first time by a two-step reduction method. Abstract : In this work, a Ni@Pt/rGO nanocomposite was prepared for the first time by a two-step reduction method. Firstly, monodisperse Pt/rGO was prepared by a solvothermal reduction of K2 PtCl4 and graphene oxide in ethylene glycol. Then, a Pt-catalyzed reduction of nickel chloride proceeded in aqueous solution at a moderate temperature of 55 °C. The thus-obtained Ni@Pt/rGO nanocomposite was characterized by transmission electron microscopy, energy dispersive X-ray analysis, X-ray diffraction and X-ray photoelectron spectroscopy. For the high surface-to-volume ratio and high catalytic ability of transition metals and graphene, an electrochemical sensor was fabricated by casting the prepared Ni@Pt/rGO composite onto the surface of a glassy carbon electrode, and the sensing properties towards glucose were evaluated. The sensor showed good detection performance with a detection limit of 8 μM and a linear range of up to 10.008 mM.